Danhong Injection Protects Against Hypertension-Induced Renal Injury Via Down-Regulation of Myoglobin Expression in Spontaneously Hypertensive Rats - John Owoicho Orgah; Miao Wang; Xiaohu Yang; Zhilong Wang; Dandan Wang; Qi Zhang; Guanwei Fan; Jihong Han; Gangjian Qin; Xiumei Gao; Yan Zhu (Karger Publishers, 2018)
Background/Aims: High blood pressure is a major risk factor for chronic kidney disease. Currently, single-target anti-hypertensive drugs are not designed for high blood pressure-related organ damages. Danhong injection (DHI), made from the aqueous extracts of Radix Salviae miltiorrhizae and Flos Carthamus tinctorius, has various pharmacological effects, including BP lowering in SHR, mediated by the reduction of vascular remodeling and the up-regulation of Kallikrein-kinin system published recently by our team, yet if it renders renal protection remains unknown. The current study demonstrated a protective role of DHI in renal injury caused by hypertension and identified its molecular targets in the kidney of spontaneously hypertensive rats (SHR). Methods: Adult SHR and age/gender-matched normotensive Wistar-Kyoto (WKY) rats were treated with DHI, Losartan, or saline for 4 weeks. Serum levels of Creatinine (CRE), Micro-albumin (mAlb), Beta2-microglobulin (β2-MG), and Uric acid (UA) were detected using ELISA kits. Renal pathology was examined by hematoxylin and Eosin (H&E) stains. Microarray analysis was performed on kidney tissues, and gene expression changes were validated by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot analyses. Results: Renal histopathological scores showed that SHR exhibited serious kidney injury compared to normotensive WKY rats. The intervention with DHI potently suppressed the renal injury biomarker (KIM-1) and kidney lesions compared to the untreated hypertensive subjects. Microarray analysis revealed that among the 124 genes that were differentially expressed by DHI treatment in SHR kidney, down-regulation of renal myoglobin (Mb) gene was the most prominent and was subsequently confirmed by qRT-PCR and Western blot analysis. Conclusion: Hypertension-induced renal injury in SHR may be alleviated by DHI in part by local suppression of Kidney injury molecule-1 and down-regulation of Myoglobin. However, if this effect is independent of the known anti-hypertensive action of DHI in blood vessel remains to be determined.